2015
DOI: 10.12693/aphyspola.128.87
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ga Addition on Structure and Magnetic Properties of the LaFe11.14Co0.66Si1.2-xGax(x=0.1, 0.2, 0.3) Alloys

Abstract: In the present work, the phase constitution and magnetic properties of the LaFe11.14Co0.66Si1.2−xGax (where x = 0.1, 0.2, 0.3) alloys, were investigated. It was revealed that increase of Ga content in the alloy composition causes the rise of lattice parameter of the La(Fe,Si)13-type phase, which causes increase of the Curie temperature. However, the increase of Ga addition leads to decrease of magnetocaloric eect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Detailed XRD studies supported by the Rietveld analysis for all annealed samples were described in our previous studies [17,18]. They revealed coexistence of two main crystalline phases: the dominant La(Fe,Si) 13 -type (193) P. Gębara and minority α-Fe(Co,Si) phase.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Detailed XRD studies supported by the Rietveld analysis for all annealed samples were described in our previous studies [17,18]. They revealed coexistence of two main crystalline phases: the dominant La(Fe,Si) 13 -type (193) P. Gębara and minority α-Fe(Co,Si) phase.…”
Section: Resultsmentioning
confidence: 67%
“…The Mössbauer studies revealed paramagnetic state of the La(Fe,Si) 13 -type phase at room temperature for all the investigated specimens, which shows that the Curie temperature of this phase is lower than room temperature. Detailed Curie temperature investigations were described in our previous works [17,18].…”
Section: Resultsmentioning
confidence: 99%
“…Fe-based alloys are usually classified as a promising group of engineering materials due to their physicochemical properties and relatively low cost of production [1,2]. These alloys show attractive soft magnetic behavior and can be used as precursors for the preparation of nanocrystalline alloys [3].…”
Section: Introductionmentioning
confidence: 99%
“…The search for new magnetocaloric material for commercial applications has concentrated mainly around the tunable T C and reasonable changes of magnetic entropy (∆S M ) [7].…”
Section: Introductionmentioning
confidence: 99%